Analisis dan perancangan aplikasi Augmented Reality anatomi tubuh manusia berbasis Android - Nurwicaksono, Ahmad Soni; Swalaganata, Galandaru (Journal of Information System and Application Development, 2023)
This study focuses on designing and analyzing an Android-based Augmented Reality (AR) device for practical learning of human anatomy. Its objective is to analyze the effectiveness of AR technology in enhancing practical learning of human anatomy and identifying possible issues in implementing such technology. The study utilizes the software development method based on SDLC with a waterfall model. The results demonstrate that the use of AR technology in practical learning of human anatomy can improve the effectiveness of student learning. Students who use AR devices can better understand and recall the material faster than those who do not. Additionally, the AR device facilitates students in visualizing the human body structure interactively and in 3D. However, the study also identifies some issues that may arise during the implementation of AR technology in practical learning of human anatomy. Educators and software developers can take note of these issues when developing AR applications for practical learning of human anatomy. In conclusion, this study proves that the use of AR technology in practical learning of human anatomy can enhance the effectiveness of student learning and provide useful information for educators and software developers in developing effective AR applications for practical learning of human anatomy.